RESEARCH OF PSYCHOLOGICAL PECULIARITIES OF WOMEN IN PRECONCEPTION PREPARATION TO PREVENT THEIR PSYCHOSOMATIC DISORDERS DURING THE PREGNANCY - Bondarenko, Natalia; Narytnyk, Tetiana; Slobodianyk, Oleh; Ziatdinova, Mariana (PSYCHOLOGICAL JOURNAL, 2018)
Perform a brief theoretical analysis of the topic: how the physiological pregnancy proceeds, how the change in the hormonal background during fertilization and in the period of bearing the fetus affects the woman’s emotional state. The work examines the psychological state and traits of the nature of women before conception and how this set of psychological qualities can affect the course, at the end of pregnancy and after birth, with a view to their possible correction in pre-school preparation. Significant role is paid to the accentuation of character, its relation to the appearance of qualitative path psychological changes at the time of pregnancy and after it. We consider the probability of occurrence of a mental illness in connection with the birth of a child. We develop methods of prevention and prevention of the emergence of mental states; studying prenatal matrices, as aiding a newborn mother in building a happy future for her child. The psychic states combined the characteristics of mental processes and the characteristics of personality features. The analysis of the mental state allows to predict the behavior of the individual, its development and self-development. On the basis of mental process that dominated by women before pregnancy, psychic property is increasing and provokes the appearance mental states, which leads to the psychosomatic illness and the pathological course of pregnancy. So its possible to prevent the appearance of psychosomatic diseases and to give birth to a healthy child by researching the psychological peculiarities of non-pregnant women and by the timely detection of a pathologically altered mental state. Confirmed that by exploring the psychological peculiarities of non-pregnant women and the timely detection of a pathologically altered mental state, in the implementation of these knowledge in pregravidinary preperation, it is possible to prevent the emergence of psychosomatic diseases and to give birth to a healthy child.